Bicentric Bipolar Prosthesis in Non-Traumatic Hip Pathologies: Maximum 10 Years Follow Up - Jha, Subash Chandra; Rai, Anil Kumar; Shakya, Prakash (Birat Journal of Health Sciences, 2018)
Introduction: Introduction of bipolar prosthesis was basically made for the treatment of fresh fracture neck of femur in elderly, but with advancement in design and techniques its use has been increased to various non-traumatic hip pathologies. Objective: To assess clinical and radiological outcome of BHU bicentric bipolar hip prosthesis in treatment of non-traumatic hip pathology. Methodology: This longitudinal study was done in 30 cases of various hip conditions, during the period of March 2002 to March 2012. All patients had secondary osteoarthritis of hip with abnormal acetabulum following advanced tubercular arthritis, rheumatoid arthritis, ankylosing spondylitis and avascular necrosis of femoral head. Primary bipolar hemi-replacement arthroplasty was done in all the cases using Banaras Hindu University (BHU) bicentric bipolar hip prosthesis. Each patient was assessed radiologically for movement and fraction of it occurring at various components of prosthesis and clinically for functional outcome using modified Harris hip score for the maximum of 10 years. Results: There were 17 males and 13 females (n=30), aged between 31-60 years. Three and half years following surgery, (n=12) 100% patients were able to squat and sit crossed legged. At four and half years follow-up, (n=7) 100% patient had excellent result when assessed by modified Harris hip score. Radiologically, by the end of 10 years (n=1) all the movements of hip occurred at inner bearing while the outer bearing was fixed to acetabulum. Conclusion: This intermediate term follow-up study suggests that the use of BHU bicentric bipolar hip prosthesis for bipolar hemireplacement is associated with be